Interaction of radiosensitizers and WR-2721. I. Modification of skin radioprotection. - Rojas, A. (Nature Publishing Group, 1982)
We have studied the radiomodifying action in mouse skin of WR-2721 and misonidazole (MISO) when used alone or in combination. The radioprotection with WR-2721 was drug-dose dependent and highly influenced by the O2 concentration at the time of irradiation. Significant sensitizaton was observed with MISO, especially in air-breathing mice. The combination of WR-2721 and MISO produced a radiation response intermediate between the resistant and sensitive responses to either drug alone. The precise degree of sensitivity was dependent on the relative doses of protector and sensitizer. We have also studied the interaction of both drugs in terms of drug-induced lethality, which showed a clear toxic interaction. The WR-2721 LD50 was reduced by a factor of 1.4 with only 200 mg/kg of MISO. We conclude that the combination of WR-2721 and MISO shows an interaction in terms of drug toxicity and radiation response, such that the radioprotection of skin is reduced or even abolished with low doses of MISO.